2011
DOI: 10.1159/000330852
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Induces Epithelial-to-Mesenchymal Transition in Rat Kidneys and Human Proximal Tubular Cells

Abstract: Background/Aims: Indoxyl sulfate (IS) is a uremic toxin that accelerates the progression of chronic kidney disease (CKD). This study aimed to determine if IS induces epithelial-to-mesenchymal transition (EMT) in the kidneys of hypertensive rats and human proximal tubular cells (HK-2). Methods: EMT was evaluated by immunohistochemistry, reverse transcription-polymerase chain reaction and immunoblotting of the epithelial markers E-cadherin and zonula occludens-1 (ZO-1), and the mesenchymal marker α-smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 37 publications
2
64
1
Order By: Relevance
“…The following cell and organ systems were investigated (n of each study is in parentheses) ( Table 2): renal tubules (9), 34,[36][37][38][39]43,45,47,50 endothelium (6), [26][27][28][29][30]33 leukocytes (2), 30,31 whole vessels (2), 40,41 whole kidney (2), 40,42 cardiac cells (2), 35,49 smooth muscle cells (2), 46,51 hepatocytes (2), 32,51 intestinal cells (1), 48 and adipocytes (1). 44 A few studies concentrated on more than one target system: one study was on both the whole vessel and kidney 40 and one study was on leukocyte-endothelial interaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following cell and organ systems were investigated (n of each study is in parentheses) ( Table 2): renal tubules (9), 34,[36][37][38][39]43,45,47,50 endothelium (6), [26][27][28][29][30]33 leukocytes (2), 30,31 whole vessels (2), 40,41 whole kidney (2), 40,42 cardiac cells (2), 35,49 smooth muscle cells (2), 46,51 hepatocytes (2), 32,51 intestinal cells (1), 48 and adipocytes (1). 44 A few studies concentrated on more than one target system: one study was on both the whole vessel and kidney 40 and one study was on leukocyte-endothelial interaction.…”
Section: Resultsmentioning
confidence: 99%
“…44 A few studies concentrated on more than one target system: one study was on both the whole vessel and kidney 40 and one study was on leukocyte-endothelial interaction. 30 Twenty-four studies concentrated on indoxyl sulfate, [26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][42][43][46][47][48][49][50][51][52] and six studies concentrated on p-cresyl sulfate. 31,34,36,39,44,45 Three studies evaluated both compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IS has a strong pro-oxidative activity by inducing reactive oxygen species (ROS) production. Recent studies, including our own, revealed that IS-induced oxidative stress cannot only damage renal cells and aggravate the progression of CKD, [16][17][18] but also has harmful effects on other tissues, such as inducing vascular endothelial damage and myocardial hypertrophy. 19,20 In addition, serum IS associates with dialysis graft thrombosis after endovascular interventions.…”
Section: Introductionmentioning
confidence: 85%
“…The secreted TGF-β1 stimulates the production of TIMP-1 and collagen. The damaged tubular cells are transformed into myofibroblasts through an epithelial-to-mesenchymal transition (14), these changes facilitate interstitial fibrosis. Thus, indoxyl sulfate accumulated in uremic serum accelerates tubular cell injury, and induces subsequent interstitial fibrosis, thus acting as a nephrotoxin.…”
Section: Nephrotoxicity Of Indoxyl Sulfatementioning
confidence: 99%